If He's Daring - Howell, Hannah (New York, NY Kensington Publishing Corp., 2014)
"Stealing a strangers carriage is the second most reckless thing Lady Catryn Gryffin de Warrene has ever done. The first is succumbing to her powerful attraction to the carriages owner. Catryn has heard the rumors about Sir Orion Wherlockes family and their otherworldly gifts. Hes the one person who can keep her son and his inheritance safe from her late husbands ruthless brother. As for how to protect herself...it may be too late for that. Orion is facing the worst danger a man of his ilk can find: a woman he cant walk away from. Catryn is an intoxicating blend of innocence and sensuality, and for the first time, seduction is far more than a game. But her beauty and fortune have made her a target - one that will dare him to risk everything hes known - in pursuit of everything hes ever longed for..."--Page 4 of cover.
Keywords: Psychic ability -- Fiction; Inheritance and succession -- Fiction; Man-woman relationships -- Fiction; England -- Social life and customs -- 18th century; Fiction; Romance fiction; Historical fiction